Gene Expression and Methylation Levels of PCSK9 Gene in Iraqi Patients with Coronary Artery Disease - Marwa M. Al-Attar; Salwa J. Al-Awadi Al-Awadi; Shaimaa Y. Abdulfattah (مجلة بغداد للعلوم)
The expression of the Proprotein Convertase Subtilisin/Kexin Type 9 gene (PCSK9) is inextricably related to lipid levels and a risk of atherosclerotic coronary artery disease (ASCAD). The present study aims to measure the quantity of PCSK9 gene expression and the effect of methylation on its expression level taking part in the pathogenesis of acute coronary artery disorder.